Sarcopenia: A Major Challenge in Elderly Patients with End-Stage Renal Disease - Maciej Domański; Kazimierz Ciechanowski (Journal of Aging Research)
Sarcopenia is a condition of multifaceted etiology arising in many elderly people. In patients with chronic kidney, the loss of muscle mass is much more intensive and the first signs of sarcopenia are observed in younger patients than it is expected. It is associated with the whole-body protein-energy deficiency called protein-energy wasting (PEW). It seems to be one of the major factors limiting patient's autonomy as well as decreasing the quality of life. If it cannot be treated with the simple methods requiring some knowledge and devotion, we will fail to save patients who die due to cardiovascular disease and infection, despite proper conduction of renal replacement therapy. Many factors influencing the risk of sarcopenia development have been evaluated in number of studies. Many studies also were conducted to assess the efficacy of different therapeutic strategies (diet, physical activity, hormones). Nevertheless, there is still no consensus on treatment the patients with PEW. Therefore, in the paper we present the reasons and pathophysiology of sarcopenia as an important element of protein energy wasting (PEW) in elderly patients suffering from chronic kidney disease. We also analyze possible options for treatment according to up-to-date knowledge.